Survey on phishing detection research - Xi FU; Hui LI; Xingwen ZHAO (网络与信息安全学报)
With the continuous development of the internet,the threat posed by phishing to people's daily lives is increasing.As a core security technology against phishing attacks,phishing detection technology can help people effectively avoid security threats caused by phishing attacks.Firstly,starting with the basic concepts of phishing,the current application scenarios of phishing identification were summarized.Then,the research status of phishing identification technology in detail were analyzed.Finally,possible future research directions were discussed.